Spontaneous atrial fibrillation in a freestyle skier. Issue 2 (23rd March 2004) - Whyte, G; Stephens, N; Sharma, S; Shave, R; Budgett, R; McKenna, W J
Abstract : A male freestyle skier was found to have atrial fibrillation during a routine physiological assessment. This was found to be associated with the consumption of an unusually large amount of alcohol. Athletes should be counselled about the potential dangers of alcohol consumption before exhaustive exercise.